1997
DOI: 10.1111/j.1469-8749.1997.tb07462.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental outcomes in children receiving resection surgery for medically intractable infantile spasms

Abstract: Two‐year postsurgical developmental outcomes were assessed in 24 children with infantile spasms who underwent resective surgery. The mean age of onset of infantile spasms was 12.0 weeks and the mean age at surgery was 20.8 months. Developmental outcomes were assessed using the Vineland Adaptive Behavior Scales (VABS). There was a significant increase in developmental level at 2 years postsurgery compared with presurgical levels. At 2 years postsurgery only one of the children in this series was severely retard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(58 citation statements)
references
References 18 publications
2
55
0
1
Order By: Relevance
“…Our results indicate that the presence of infantile spasms at presentation should urge prompt medical and perhaps surgical intervention. To this effect, Asarnow et al [4] demonstrated that the 2-year postsurgical developmental outcomes of infants were best for the infants who underwent surgery when they were relatively young and who had the highest level of developmental performance presurgically, again supporting the idea that earlier intervention may halt epileptogenesis-related developmental deterioration.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our results indicate that the presence of infantile spasms at presentation should urge prompt medical and perhaps surgical intervention. To this effect, Asarnow et al [4] demonstrated that the 2-year postsurgical developmental outcomes of infants were best for the infants who underwent surgery when they were relatively young and who had the highest level of developmental performance presurgically, again supporting the idea that earlier intervention may halt epileptogenesis-related developmental deterioration.…”
Section: Discussionmentioning
confidence: 97%
“…Few available reports have evaluated the intellectual outcome in infants who have undergone epilepsy surgery [4], [11], [13] and [14]. According to results presented by Daniel et al, neuropsychological performance after surgery was best for children who underwent surgery at a younger age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations